Model Architecture Software for Geospatial based Augmented Reality - Johan Reimon Batmetan; Trudi Komansilan; Sondy Kumajas; Hiskia Kamang Manggopa (JR Education, 2022)
Software architecture is the basis of every software system and is very important used in software development. Augmented reality (AR) can make it easier for users to interact with virtual objects in a real environment through a camera display that displays 3D objects. In the tourism industry, augmented reality can be used to display the geographical location of tourist attractions, routes to locations, and 3D shapes of buildings that make it easier for users when looking for the nearest tourist destination. Designing an application in this case G-STAR requires several things, namely: Description of needs: Product perspective, product function, user characteristics, both developers and tourists. Specific needs: External interface requirements, namely user interfaces, hardware interfaces, software interfaces, communication interfaces. Software functionality requirements: Application flowchart. Functional requirements specification: Menu feature, function, camera AR function, tourist attraction function, Map function, info function, and guide function. Sequence diagrams. User interface/application prototyping.